2016
DOI: 10.1007/s00268-016-3514-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Parathyroidectomy in Patients with Primary Hyperparathyroidism: A Systematic Review and Meta‐analysis

Abstract: MIP and BNE are both effective surgical techniques for the treatment of primary hyperparathyroidism. The safety profile of MIP appears superior to BNE (lower rate of hypocalcemia and recurrent laryngeal nerve injury).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 138 publications
2
60
3
1
Order By: Relevance
“…Our data is completely consistent with the findings from large systematic reviews and meta‐analyses evaluating MIP and bilateral neck exploration (BNE) including one completed by Ospina and colleagues in 2016. In their meta‐analysis of 88 published studies, cure rates were reported to be 97% for MIP and 98% for BNE with four‐gland dissection . Of note, hypocalcemia occurred in 14% of BNE cases versus 2.3% in MIP cases, and there was also a statistically significant lower risk of laryngeal nerve injury with MIP compared to BNE (0.3% vs. 0.9%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data is completely consistent with the findings from large systematic reviews and meta‐analyses evaluating MIP and bilateral neck exploration (BNE) including one completed by Ospina and colleagues in 2016. In their meta‐analysis of 88 published studies, cure rates were reported to be 97% for MIP and 98% for BNE with four‐gland dissection . Of note, hypocalcemia occurred in 14% of BNE cases versus 2.3% in MIP cases, and there was also a statistically significant lower risk of laryngeal nerve injury with MIP compared to BNE (0.3% vs. 0.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that image‐guided, ioPTH‐assisted minimally invasive parathyroidectomy (MIP) results in cure rates equivalent to that of conventional BNE with four‐gland dissection . Despite this, a parathyroid surgical group based, which had previously been staunch proponents of minimally invasive parathyroid surgery (calling “bilateral neck exploration for all parathyroid patients an operation for the history books”), changed their approach in 2012 and now are dogmatic advocates for universal BNE with four‐gland dissection .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby from classical bilateral four gland exploration of PA an increasing number of unilateral focused minimally invasive techniques have been introduced in numerous centers including open minimal parathyroidectomy but also video-guided, radio-guided and endoscopic removal of PA with or without rapid intraoperative PTH assay reducing the cost and morbidity while maintaining cure rates (27,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Both MIP and BNE have an excellent cure rate. In their recent meta-analysis, Ospina et al reported that the cure rate was 98% with BNE and 97% with MIP, with lower morbidity for MIP [18]. In a large series of patients, Lee et al reported that the major cause of operative failure was the surgeon's failure to identify abnormal glands and the absence of performing BNE in case of an inadequate decrease in intra-operative PTH levels (IOPTH) [19].…”
Section: Predictive Factors Of R-phpt or P-phptmentioning
confidence: 99%